Blockchain-Based Optimization of Raw Material Inventory: Enhancing Efficiency in Salak Sidimpuan Agricultural Production - Pulungan, Ahmad Suyuti; Harahap, Nirmala Haty; Idris, Iswandi (Journal of Science and Education (JSE), 2025)
Blockchain technology has emerged as a revolutionary tool in supply chain management, offering enhanced transparency, security, and efficiency. This study explores the implementation of blockchain technology to optimize raw material inventory management in Salak Sidimpuan agricultural production. Using data from farmers and cooperatives, the research analyzes the impact of blockchain on production efficiency, leveraging a PLS-SEM model for statistical analysis. Results indicate a significant improvement in inventory efficiency, leading to reduced costs and improved trust among stakeholders. The findings suggest blockchain as a viable solution for transforming traditional agricultural supply chains.